2018
DOI: 10.1038/s41598-018-31094-1
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and feeding induce tissue level changes in autotrophic and heterotrophic nutrient allocation in the coral symbiosis – A NanoSIMS study

Abstract: Corals access inorganic seawater nutrients through their autotrophic endosymbiotic dinoflagellates, but also capture planktonic prey through heterotrophic feeding. Correlating NanoSIMS and TEM imaging, we visualized and quantified the subcellular fate of autotrophic and heterotrophic C and N in the coral Stylophora pistillata using stable isotopes. Six scenarios were compared after 6 h: autotrophic pulse (13C-bicarbonate, 15N-nitrate) in either unfed or regularly fed corals, and heterotrophic pulse (13C-, 15N-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 85 publications
3
64
1
Order By: Relevance
“…Even though significant physiological changes were observed, the feeding treatment is likely a conservative representation of food availability on the reef, where corals have access to a quasi‐continuous availability of diverse zooplankton. In previous studies, feeding with similar diets to that used here, has been reported to increase (Treignier, Grover, Ferrier‐Pagés, & Tolosa, ), decrease (Al‐Moghrabi, Allemand, Couret, & Jaubert, ), and not change (Krueger et al, ) symbiont densities and/or Chl a concentration and the outcome likely depends on other environmental factors such as light level. Increased Chl a concentration found in this study may be an acclimation to low food conditions and low light in an attempt to increase light capture and photosynthetic efficiency.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Even though significant physiological changes were observed, the feeding treatment is likely a conservative representation of food availability on the reef, where corals have access to a quasi‐continuous availability of diverse zooplankton. In previous studies, feeding with similar diets to that used here, has been reported to increase (Treignier, Grover, Ferrier‐Pagés, & Tolosa, ), decrease (Al‐Moghrabi, Allemand, Couret, & Jaubert, ), and not change (Krueger et al, ) symbiont densities and/or Chl a concentration and the outcome likely depends on other environmental factors such as light level. Increased Chl a concentration found in this study may be an acclimation to low food conditions and low light in an attempt to increase light capture and photosynthetic efficiency.…”
Section: Discussionmentioning
confidence: 54%
“…Treignier, Grover, Ferrier-Pagés, & Tolosa, 2008), decrease (Al-Moghrabi,Allemand, Couret, & Jaubert, 1995), and not change(Krueger et al, 2018) symbiont densities and/or Chl a concentration and the outcome likely depends on other environmental factors such as light level. Increased Chl a concentration found in this study may be an acclimation to low food conditions and low light in an attempt F I G U R E 1 Parent (a-d) and planulae (e-h) physiology from fed (black) and unfed (gray) Stylophora pistillata: (a) parent host protein concentration per surface area, (b) parent symbiont cells per surface area, (c) parent chlorophyll a concentration per symbiont cell (parents fed n = 6, unfed n = 6), (d) total number of planulae released, (e) protein concentration per planula, (f) symbiont cells per planula, (g) chlorophyll a concentration per symbiont cell in planulae (n = triplicate of 20 pooled planulae per treatment), and (h) photosynthetic yield of planulae (n = 10 per treatment.…”
mentioning
confidence: 99%
“…A growing understanding of the metabolic hostsymbiont relationship has encouraged the use of methods that allow the measuring of these dynamics, such as metabolomics (Cui et al, 2019;Matthews et al, 2017) or NanoSIMS (Krueger et al, 2018). Recent studies have increasingly been combining coral and Symbiodiniaceae responses in their hypothesis testing.…”
Section: The Holistic Holobiontmentioning
confidence: 99%
“…Recent studies have increasingly been combining coral and Symbiodiniaceae responses in their hypothesis testing. A growing understanding of the metabolic hostsymbiont relationship has encouraged the use of methods that allow the measuring of these dynamics, such as metabolomics (Cui et al, 2019;Matthews et al, 2017) or NanoSIMS (Krueger et al, 2018). These have shown that the metabolic balance between the two partners is not only sensitive to environmental stressors but specifically fine-tuned (Cui et al, 2019;Matthews et al, 2017;Nielsen, Petrou, & Gates, 2018).…”
Section: The Holistic Holobiontmentioning
confidence: 99%
“…Corals are meta-organisms (so-called holobionts 6 ) that host a dynamic population of bacteria, archaea, viruses and photosynthetic dinoflagellate algae (family: Symbiodiniaceae) 7 . The flux of metabolites between the host and its symbionts has been the subject of numerous studies using stable isotope labelling combined with either bulk tissue analyses 8,9 or correlative imaging [10][11][12][13][14][15] . However, these previous studies have generally focused on the photosynthetic performance of the algae and the metabolic interactions between host and symbiont population.…”
mentioning
confidence: 99%